The 808 nm Laser-Assisted Surgery as an Adjunct to Orthodontic Treatment of Delayed Tooth Eruption - Seifi, Massoud; Vahid-Dastjerdi, Elahe; Ameli, Nazila; Badiei, Mohammad-Reza; Younessian, Farnaz; Amdjadi, Parisa (Journal of Lasers in Medical Sciences, 2013)
Introduction: Failure of teeth to erupt from gingival tissues at usual developmental time is called delayed tooth eruption (DTE). Delayed tooth eruption lead to prolonged fixed orthodontic treatment and its eventual complications. The purpose of the present study was to evaluate the effect of laser-assisted (808 nm) surgical uncovering, on the tooth emergence and orthodontic treatment of DTE. Methods: A total of 16 orthodontic patients were included in this study and were equally assigned to an experimental and a control group. Subjects for experiment consisted of eight patients (6 girls and 2 boys) with a mean age of 14±0.9 years. All patients exhibited delayed second premolar eruption. The laser wavelength was 810 nm and it was set in a continuous wave mode at a power output of 1.6 watt with a 0.3-mm diameter fiber tip. When the target tissue was sufficiently anesthetized, the tip was directed at an angle of 10 to 20 degrees to the tissue (light contact mode); and was applied continuously for approximately 12 Seconds until an acceptable tooth exposure area was visible. The facial axis of the clinical crown (FACC) line represents the most prominent portion of the facial central lobe for premolars. All orthodontic brackets are aligned along this reference and are located on FA (Facial Axis) point. The standard for adequate tooth eruption was the accessibility of facial axis of the clinical crown (FACC) for bonding the brackets. Data gathered from the patients were statistically surveyed and compared by means of Tukey’s Test and Analysis of Variance (ANOVA). Results: All patients showed good gingival status, no significant bleeding during or immediately after the surgery, and acceptable level of healing after laser surgery. The biologic width of the teeth was preserved and no violation of this important periodontal parameter was observed. The average time for accessing the FA point in experimental group was 11±1.1 weeks and the mentioned period was increased to 25±1.8 weeks in control group. The data analysis showed that in patients with DTE, laser intervention significantly accelerated tooth eruption (P < 0.05). Conclusion: Laser-assisted surgical removal of the fibrous tissue over erupting premolars (DTE) with appropriate irradiation parameters appears to be a promising adjunct to orthodontic treatment for bringing the premolar to the aligned and leveled dental arch.